The effect of oxidized low-density lipoprotein combined with adriamycin on the proliferation of Eca-109 cell line - Cui Jia; Wang Mei; Wang Ping; Li Qing D; Li Hao; Diao Tao; Li Qing (Lipids in Health and Disease, 2011)
Abstract Background The purpose of this study was to identify the affect on the proliferation Eca-109 cells treated with oxidized low-density lipoprotein (ox-LDL) combined with adriamycin (ADM). Methods Eca-109 cell were cultured in the presence of oxLDL/ADM, and cell proliferation tested by MTT and cell apoptosis was monitored by the proportion of apoptosis and cell cycle by flow cytomester. We simultaneously evaluated the level of associated- apoptosis Bcl-2, Bax, and Caspase-3 gene mRNA and protein. Results OxLDL were cytotoxic and activate apoptosis. OxLDL combined with ADM significant enhanced the proportion rate of apoptosis on a time and dose dependency. The expressions of the inhibiting apoptosis Bcl-2 gene mRNA and protein were down regulated, whereas, the expressions of the promoting apoptosis Bax, and Caspase-3 genes mRNA and protein were up regulation. Conclusion These results suggested that oxLDL have cytotoxicity and activate apoptosis on the Eca-109 cells. OxLDL combined with ADM have a synergistic effect on the apoptosis induced Eca-109 cells. Furthermore, oxLDL may contribute to the improvement of clinical chemotherapy of cancer need to make further investigation.